Marine conservation area in Sabah: the roles and contributions of Sabah parks in establishing and managing the Tun Mustapha Park (TMP) / Erica Joanne Reuben and Haijon Gunggut - Reuben, Erica Joanne; Gunggut, Haijon (Universiti Teknologi MARA, 2021)
The biggest marine conservation area in Malaysia, Tun Mustapha Park (TMP), was finally been established on May 19, 2016. This study focuses on the roles and contribution of Sabah Park in the process of gazetitng the Tun Mustapha Park (TMP). The study is important in order to understand the scope of work of Sabah Park as the lead actor involved in establishing TMP. This study used qualitative approach where most of the data were obtained from literary sources. The main scope of work of Sabah Park in the process of establishing TMP are managing the overall initiative to establish TMP Steering Committee including in fisheries management, marine habitat protection through collaborative management, shoreline management and control of land-based pollution, livelihoods and enterprise management, and education and awareness. Thus, the guidance of Sabah Park has been crucial in the agenda setting of the TMP as well as the completion of more than 13 years of negotiation, lobbying, capacity building, scientific discovery and community outreach before the establishment of TMP.